Evaluation of Dimensions and Drainage Performance Office in the Aceh Tamiang Area Kuala Simpang - Kamaluddin Lubis (Britain International of Exact Sciences (BIoEx) Journal, 2021)
The Aceh Tamiang office area is one of the office areas in Kuala Simpang which consists of various offices in the Aceh Tamiang area. The purpose of this research is to identify the drainage condition of the existing primary drainage channel which accommodates runoff discharge, the shape and direction of the flow in the inundation channel in the Aceh Tamiang Kuala Simpang office area, which is expected to help solve the problem of flooding in the 832 m3 / second. And for the channel capacity in this primary drainage drainage of 0.829 m3 / sec, the value is smaller than the planned flood discharge (Qr). Rainfall intensity (I) of 126,432 mm / hour. The plan flood discharge (Qr) for a 5-year return period yields 2,551 m3 / second and the value for channel discharge capacity (Qs) is obtained from the calculation of 2,216 m3 / second. This value is smaller than the value of the planned flood discharge.area. From the results of research conducted by the Aceh Tamiang Kuala Simpang office area is a location with a fairly high degree of rainfall, with a rainfall intensity (I) of 126,432 mm / hour and a flood discharge plan for a 5-year return period obtained a result of 0.